Europe, idea of a continent: The quest for the European identity - van der Wal, Koo (Creativity Studies, 2008)
Against a widespread scepticism with regard to the existence of a European identity, the article maintains both that there is such a thing as European culture and mentality or European “story”, and that there has to be one, if European economy, law and politics are to be successful in the longer run. The article attempts to show ideal‐typically that there is quite a series of interconnected common features (institutions, practices, convictions and guiding ideas) on the European continent. This can also be made visible in the contrast with non‐western cultures, and within the western cultural area with the American society and mentality as well. It is not denied that the European “story” is often distorted by a stubborn reality (power relations, conflicts of interests, etc.). Nevertheless, it is constantly working on all levels of the European society and offers guidance to the processes at work there.Europos kontinento idėja: europietiškosios tapatybės paieškosSantrauka. Atsitolinama nuo plačiai paplitusio skepticizmo ir laikomasi pagarbios pozicijos europietiškosios tapatybės atžvilgiu. Tvirtinama, kad egzistuoja tiek europietiškoji kultūra ir mentalitetas kaip tam tikras europietiškasis „pasakojimas“, tiek Europos ekonomika, teisė ir politika. Bandoma parodyti, kad šiuolaikinėje Europoje gali būti aptinkama gana daug tam tikrų glaudžiai susijusių institucijų, veiklos rūšių, įsitikinimų ir vyraujančių idėjų. Tai siekiama išryškinti, europietiškąją kultūrą supriešinant su nevakarietiškosiomis bei su Amerikos visuomene ir mentalitetu. Straipsnio autoriaus manymu, europietiškasis „pasakojimas“ nūdienėje epochoje neretai vis dar iškraipomas sustabarėjusių galios santykių ir interesų konfliktų, todėl turi būti iš naujo apmąstomas ir interpretuojamas šiuolaikinio socialinio bei filosofinio mąstymo perspektyvoje.Reikšminiai žodžiai: kultūrinis veiksnys, demokratija, europietiškasis „pasakojimas“, ne-demoso argumentas, visuomenės diferenciacija.First Published Online: 14 Oct 2010